Estimasi Tingkat Kebisingan pada Airfoil dengan Penerapan Metode Neural Network dan Bagging - Setiyorini, Tyas (Jurnal Teknik Informatika, 2017)
Noise on aircraft, especially unmanned aircraft becomes the problem that became the concentration of research from year to year. Noise is an unwanted noise, as it causes disruption to human comfort and health. Most of the noise on the plane comes from the propeller system of the lifter, rotor, and engine. In general, one of the parameters that affect the noise caused by the propeller is the basic geometry of the propeller-forming airfoil. Airfoil datasets have non-linear properties. The high variance in the airfoil dataset also shows high noise. Neural network method has good performance in overcoming nonlinear data problem, but neural network has weakness in overcoming high noise data. To solve the problem a bagging method is needed to reduce the high noise indicated by the high variance on the airfoil dataset. Several experiments were conducted to obtain optimal architecture and produce accurate estimates. The experimental results of the 8 combinations of research parameters on the airfoil dataset with the neural network obtained the smallest RMSE value was 2.071, while using neural network and bagging obtained the smallest RMSE value was 1.718. It can be concluded that the estimated noise level in airfoil using bagging and neural network method is more accurate than the individual neural network method.Ã‚Â Ã‚Â IntisariÃ¢â‚¬â€Sebagian besar kebisingan pada pesawat berasal dari sistem propeller pengangkat, rotor, dan mesin. Secara umum, salah satu parameter yang mempengaruhi kebisingan yang disebabkan oleh propeller adalah geometri dasar pembentuk propeller yaitu airfoil. Dataset airfoil memiliki sifat non linear. Varians yang tinggi pada dataset airfoil juga menunjukkan tingginya noise. Metode neural network memiliki kinerja yang baik dalam mengatasi masalah data nonlinear, namun neural network memiliki kelemahan dalam mengatasi data noise yang tinggi. Untuk menyelesaikan masalah tersebut diperlukan metode bagging untuk mengurangi tingginya noise yang ditunjukkan dari varians yang tinggi pada dataset airfoil. Beberapa eksperimen dilakukan untuk mendapatkan arsitektur yang optimal dan menghasilkan estimasi yang akurat. Hasil eksperiman dari 8 kombinasi parameter penelitian pada dataset airfoil dengan neural network didapatkan nilai RMSE terkecil adalah 2.071, sedangkan dengan menggunakan neural network dan bagging didapatkan nilai RMSE terkecil adalah 1.718. Maka dapat disimpulkan estimasi tingkat kebisingan pada airfoil dengan menggunakan metode bagging dan neural network lebih akurat dibanding dengan metode individual neural network.Ã‚Â  Ã‚Â Kata KunciÃ¢â‚¬â€ Estimasi, Tingkat kebisingan Airfoil, Neural